A novel Lyapunov-based trajectory tracking controller for a quadrotor: Experimental analysis by using two motion tasks. (August 2019) - Pérez-Alcocer, Ricardo; Moreno-Valenzuela, Javier
Abstract: A novel model-based controller for quadrotor trajectory tracking is presented in this paper. The closed-loop stability is studied by Lyapunov's theory guaranteeing local asymptotical stability of the resulting equilibrium point. The performance of the proposed scheme is compared in real time with respect to three known trajectory tracking controllers having different structures. Besides, two desired trajectories encoding different motion tasks are specified. The gains of the tested controllers are selected so that the mean value of the total thrust is the same. An analysis by using different performance indexes is employed in order assess the tracking performance of each scheme. The proposed controller presents the best experimental execution for the two implemented motion tasks.